LASER TECHNOLOGIES – MASTER’S PROGRAM BETWEEN TWO EUROPEAN UNIVERSITIES OF APPLIED SCIENCES FROM LATVIA AND GERMANY - Vilkaste, Aivars; Lazov, Lyubomir Kostadinov; Deneva, Hristina; Teirumnieka, Erika; Teirumnieks, Edmunds; Narica, Pāvels (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Laser equipment and laser technologies are among the most modern, fastest growing and most promising branches of science and technology in the 21st century. The first laser was created in 1960 and for about 55 years, today there is hardly any area of our lives in which lasers and related technologies are not applied. Laser systems and related innovative technologies ensuring high precision, productivity and quality of production have been developed and proposed worldwide from hundreds of scientific research institutes and companies. The Master's program is accredited in two European universities in Germany and Latvia and allows for the production of double diplomas. The course is based on international experience and reflects the most recent advances in laser techniques and technologies. The program examines the physical fundamentals and technical realization of various types of laser systems and their specific characteristics. First the necessary foundations of the laser physics, optics and the interaction of radiation with matter are presented, followed by more detailed examination of the problems of laser technology in various fields of science, technology and industrial production. Basic physical and technical solutions of the building blocks of lasers are presented in details, such as: optical resonators, active environments, excitation systems, management systems, laser generation. As well as specific issues and practical examples of industrial applications are described.